The best American comics 2018 - Gloeckner, Phoebe 1960- (The best American series, 2018)
Best American Comics 2016 showcases the work of both established and up-and-coming contributors and highlights both fiction and nonfiction from graphic novels, pamphlet comics, newspapers, magazines, minicomics, and the Web to make a collection that is full of varied, provocative feats of cartooning